SISTEM INFORMASI BERBASIS WEB UNTUK MONITORING DAN EVALUASI SENTRA INDUSTRI KECIL ALAS KAKI DI JAWA BARAT - Rizki Wahyuniardi; Leni Herliani Afrianti; Sidik Nurjaman; Wanda Gusdya (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2015)
The use of web-based information system has been widely applied in various fields. Speed, precision, and accuracy are the advantages of this application. After conducting the initial assessment, it was found that the monitoring and evaluationpolicy has not been optimal in its implementation.Cost is the main constraint in this activity. Therefore, we needed a web-based information system in order to solve these problems. This study was made with the aim of speeding up the process of monitoring and evaluation of small medium entreprises (SMEs) footwear in the province of West Java, especially in district of Tasikmalaya, Bandung, and West Bandung. Based on the collection and processing of data, it is shown that SMEs in the district of Bandung, West Bandung and Tasikmalaya are Stars 2 category.